Knowledge, attitudes and practices of male circumcision as an HIV prevention method among males in a Mine, Geita, Tanzania - Mubekapi, Constance (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.